2014
DOI: 10.1021/om4006214
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Carbene and Carbyne Formation in Molybdenum(0) and Tungsten(0) Dinitrogen Complexes

Abstract: Zerovalent group 6 dinitrogen phosphine complexes react with 3,3-diphenylcyclopropene to give vinylcarbyne hydride complexes that have been characterized crystallographically. Computational studies indicate that the observed products resulted from the α-migration and rearrangement of an initially formed vinylcarbene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Triethyloxonium tetrafluoroborate [19] was prepared according to a reported literature procedure. The reagents [Mo(CO) 6 ], n-butyl lithium (1.6 M solution in hexane), furan, 1,2-bis(diphenylphosphino)ethane (dppe), PPh 3 , cyclohexyl amine (NH 2 Cy) and other commercial reagents were used as purchased. NMR spectra were recorded on a Bruker ARX-300.…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…Triethyloxonium tetrafluoroborate [19] was prepared according to a reported literature procedure. The reagents [Mo(CO) 6 ], n-butyl lithium (1.6 M solution in hexane), furan, 1,2-bis(diphenylphosphino)ethane (dppe), PPh 3 , cyclohexyl amine (NH 2 Cy) and other commercial reagents were used as purchased. NMR spectra were recorded on a Bruker ARX-300.…”
Section: Generalmentioning
confidence: 99%
“…Furan was monolithiated at À30°C with n-BuLi in THF as solvent. Subsequent reaction with Mo(CO) 6 , followed by alkylation in dichloromethane, yields the desired pentacarbonyl carbene complex. Aminolysis of 1 with either cyclohexyl amine or ammonia in diethyl ether, led to the formation of 4 and 7, respectively.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These complexes contained a chiral biphosphite ligand and it was shown that the fac isomer could be converted to the mer isomer under thermal conditions. Ning et al [8] found that by using group VI metal compounds, specifically chromium and molybdenum compounds containing dinitrogen and phosphine ligands, the synthesis of a vinylcarbyne hydride complex, via a vinylcarbene intermediate, could be achieved. The synthesis and structure of a series of molybdenum-Fischer carbene complexes [4,9] and bimetallic carbene complexes of molybdenum with multiple thiophene rings as bridging units have been reported by Landman et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…1521, Scheme 124) were prepared from the reaction of the dinitrogen complex 1518 with 3,3-diphenylcyclopropene (1519) [1312]. A mechanism that involves M a n u s c r i p t 183 formation of an agostically-bound carbene complex (1520) followed by α-hydride elimination was proposed and supported through DFT studies.…”
Section: B Synthesis And/or Generationmentioning
confidence: 98%